Epicarideos de Baja California: distribución y notas ecológicas de Probopyrus pandalicola (Packard, 1879) en el Pacífico oriental. - Campos, Ernesto (1989)
The distribution of Probopyrus pandolicola (Packard, 1879), (hast. Palaemon ritteri Holmes), is extended from Río Chiriquí, Península Burica, Panamá, to near Puertecitos, Baja California (Gulf of California), México. A greater percentage of male than female hosts are infested (P < 0.0001), but larger females (carapace length more than 6.5 mm) were most heavily infested. Female P. pandalicola present a random distribution (coefficient of dispersion s2/x near to 1) throughout the host population, which is "atypical" to the host-bopyrid relationship, All infested hosts carried only a female parasite each. We suspect that P. pandalicola is exotic for the Pacifico A list of the epicaridean isopods recorded from the Mexican Pacific is included.